Stratification of the Radiation Field inside a Photobioreactor during Microalgae Growth - Heinrich, Josué Miguel (2013)
Light availability is a main issue in autotrophic growth of photosynthetic microorganisms. The changeofthe suspended cells concentration and that of their chlorophylls content during microalgal growth alters the optical properties of the aqueous suspension.This brings about changes in the properties of the radiation field inside the reactor. In this work,we have computed the evolution in time of the local flux density,as well asthat of the local volumetric rateof absorption of photons inside a photobioreactor by means of a Monte Carlo simulation algorithmpreviously developed.From this study we have computed two operational variables that areusefultoolsfor the analysis, performance comparison, optimization and scaling-up of photobioreactors: the average rate of photon absorption and the volumetric distribution function of photons absorption rates.Based on thesetwo variables it is possible to sistematically quantify the degree of stratification of the culture medium, which is a decisive aspect thathampers the reactor efficiency regarding the energy usage for biomass production.